2018
DOI: 10.1002/jssc.201701150
|View full text |Cite
|
Sign up to set email alerts
|

Quantification, dissipation behavior and risk assessment of ethion in green pea by gas chromatography‐electron capture detector

Abstract: Residue investigation was carried out to scrutinize the persistence, dissipation behavior, half-life, and risk assessment of ethion on green pea fruit by spraying ethion at the fruiting stage followed by another application at 10 day intervals. The samples were extracted by using a quick, easy, low-cost, effective, rugged, and safe method, and the residues of ethion were analyzed by gas chromatography with electron capture detection. Here we report a novel, accurate, and cost-effective gas chromatography metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…also observed dissipation of ethion in green pea and found it to follow first‐order kinetics with half‐life 2.47 days following application of ethion at 500 g a.i. ha −1 . Hassanzadeh, Nasrin, et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…also observed dissipation of ethion in green pea and found it to follow first‐order kinetics with half‐life 2.47 days following application of ethion at 500 g a.i. ha −1 . Hassanzadeh, Nasrin, et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ishrat et al also observed dissipation of ethion in green pea and found it to follow first-order kinetics with half-life 2.47 days following application of ethion at 500 g a.i. ha −1[19]. Hassanzadeh, Nasrin, et al also reported half-life of ethion on green house cucumbers 2.1 and 1.8 days following application of ethion at 375 and 700 g a.i.…”
mentioning
confidence: 96%
“…Therefore, RP‐HPLC appears the helpful approach of choice affording identification, separation and quantification of pesticides . In present communication with continuation of our previous studies on application of chromatography, risk assessment, persistence and simultaneous quantification of carbendazim and triazophos has been evaluated by validated reversed phase high performance liquid chromatography.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, gas chromatography (GC) appears the appropriate choice affording identification, separation and quantification of pesticides. In continuation of our previous studies [19][20][21][22][23][24][25][26][27][28] on application of chromatography for fingerprinting and chromatographic method development to assure quality control of vegetables/fruits/medicinal plants, a validated analytical method has been developed for the simultaneous quantification of eight pesticides ( Fig. 1) from apple: chlorpyrifos-methyl (1), chlorpyrifos (2), quinolphos (3), profenofos (4), myclobutnil (5), ethion (6), fenpropathrin (7) and cypermethrin (8).…”
Section: Introductionmentioning
confidence: 99%